Binding H2, N2, H-, and BH3 to transition-metal sulfur sites: synthesis and properties of [RuL(PR3)(N2Me2S2)] Complexes (L=eta2-H2, H-, BH3; R=Cy, iPr). - Heinemann, Frank Wilhelm; et al. (Chemistry - A European Journal, 2004)
The reactions of [Ru(N(2))(PR(3))('N(2)Me(2)S(2)')] ['N(2)Me(2)S(2)'=1,2-ethanediamine-N,N'-dimethyl-N,N'-bis(2-benzenethiolate)(2-)] [1 a (R=iPr), 1 b (R=Cy)] and [micro-N(2)[Ru(N(2))(PiPr(3))('N(2)Me(2)S(2)')](2)] (1 c) with H(2), NaBH(4), and NBu(4)BH(4), intended to reduce the N(2) ligands, led to substitution of N(2) and formation of the new complexes [Ru(H(2))(PR(3))('N(2)Me(2)S(2)')] [2 a (R=iPr), 2 b (R=Cy)], [Ru(BH(3))(PR(3))('N(2)Me(2)S(2)')] [3 a (R=iPr), 3 b (R=Cy)], and [Ru(H)(PR(3))('N(2)Me(2)S(2)')](-) [4 a (R=iPr), 4 b (R=Cy)]. The BH(3) and hydride complexes 3 a, 3 b, 4 a, and 4 b were obtained subsequently by rational synthesis from 1 a or 1 b and BH(3).THF or LiBEt(3)H. The primary step in all reactions probably is the dissociation of N(2) from the N(2) complexes to give coordinatively unsaturated [Ru(PR(3))('N(2)Me(2)S(2)')] fragments that add H(2), BH(4) (-), BH(3), or H(-). All complexes were completely characterized by elemental analysis and common spectroscopic methods. The molecular structures of [Ru(H(2))(PR(3))('N(2)Me(2)S(2)')] [2 a (R=iPr), 2 b (R=Cy)], [Ru(BH(3))(PiPr(3))('N(2)Me(2)S(2)')] (3 a), [Li(THF)(2)][Ru(H)(PiPr(3))('N(2)Me(2)S(2)')] ([Li(THF)(2)]-4 a), and NBu(4)[Ru(H)(PCy(3))('N(2)Me(2)S(2)')] (NBu(4)-4 b) were determined by X-ray crystal structure analysis. Measurements of the NMR relaxation time T(1) corroborated the eta(2) bonding mode of the H(2) ligands in 2 a (T(1)=35 ms) and 2 b (T(1)=21 ms). The H,D coupling constants of the analogous HD complexes HD-2 a ((1)J(H,D)=26.0 Hz) and HD-2 b ((1)J(H,D)=25.9 Hz) enabled calculation of the H–D distances, which agreed with the values found by X-ray crystal structure analysis (2 a: 92 pm (X-ray) versus 98 pm (calculated), 2 b: 99 versus 98 pm). The BH(3) entities in 3 a and 3 b bind to one thiolate donor of the [Ru(PR(3))('N(2)Me(2)S(2)')] fragment and through a B-H-Ru bond to the Ru center. The hydride complex anions 4 a and 4 b are extremely Brønsted basic and are instantaneously protonated to give the eta(2)-H(2) complexes 2 a and 2 b.